2016
DOI: 10.1164/rccm.201410-1793oc
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin I2Signaling and Inhibition of Group 2 Innate Lymphoid Cell Responses

Abstract: Rationale: Group 2 innate lymphoid cells (ILC2s) robustly produce IL-5 and IL-13, cytokines central to the asthma phenotype; however, the effect of prostaglandin (PG) I 2 on ILC2 function is unknown.Objectives: To determine the effect of PGI 2 on mouse and human ILC2 cytokine expression in vitro and the effect of endogenous PGI 2 and the PGI 2 analog cicaprost on lung ILC2s in vivo.Methods: Flow-sorted bone marrow ILC2s of wild-type (WT) and PGI 2 receptor-deficient (IP 2/2 ) mice were cultured with IL-33 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
130
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 52 publications
11
130
2
Order By: Relevance
“…Lipoxin A 4 , derived from arachidonic acid, also inhibits IL-13 production from human ILC2s (46). A recent publication reported that an analogue of prostacyclin inhibited IL-33-induced IL-5 and IL-13 production from both mouse and human ILC2s (47). Consistently, our study also indicates prostacyclin as an inhibitory regulator because iloprost directly suppressed ILC2 proliferation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Lipoxin A 4 , derived from arachidonic acid, also inhibits IL-13 production from human ILC2s (46). A recent publication reported that an analogue of prostacyclin inhibited IL-33-induced IL-5 and IL-13 production from both mouse and human ILC2s (47). Consistently, our study also indicates prostacyclin as an inhibitory regulator because iloprost directly suppressed ILC2 proliferation.…”
Section: Discussionsupporting
confidence: 88%
“…Consistently, our study also indicates prostacyclin as an inhibitory regulator because iloprost directly suppressed ILC2 proliferation. As demonstrated in the report (47), IP-mediated signaling could be a new target for regulating ILC2s in the treatment of allergic diseases.…”
Section: Discussionmentioning
confidence: 89%
“…IL-5 production is imperative for infiltration of eosinophils into the airway, a key pathologic feature of allergy, and IL-13 is important for increased airway hyperresponsiveness and mucus production (Halim et al, 2012a). ILC2 secrete more IL-5 and IL-13 compared to CD4+ T cells and are also important for establishing a memory Th2 allergic response in the lung and skin, underscoring the substantial pathophysiologic potential of ILC2 (Halim et al, 2014; Klein Wolterink et al, 2012; Zhou et al, 2016). …”
mentioning
confidence: 99%
“…Similar detrimental roles of IL-13-producing ILC2s were demonstrated in a mouse model of C. neoformans -induced airway inflammation [126] and in patients with Aspergillus -mediated chronic sinusitis [127]. Interestingly, prostaglandin I2 can reduce the number of Th2-expressing ILC2 in the lung, such as IL-13 and IL-5, and could potentially be exploited as a therapeutic strategy in this context [128]. …”
Section: Innate Lymphocytesmentioning
confidence: 69%